Internalization of character education values in Arabic Language learning for Tsanawiyah Students Dayah Al Muslimun Lhoksukon North Aceh - Syukran, Syukran; Sutaman, Sutaman; Arifa, Zakiyah; Nurmala, Mia (Directorate of Research and Community Service, Universitas Negeri Yogyakarta, 2024)
This study aims to describe the implementation of character education values and their internalization in Arabic language learning for tsnawiyah students of Dayah Al Muslimun Lhoksukon North Aceh. This research uses descriptive qualitative methods, and the data collected are the results of observations, interviews and documentation. Data analysis in this study used Miles & Huberman's interactive analysis theory. The data analysis technique in this study begins with collecting data, presenting, reducing and concluding. The results of this study indicate that the value of character education values contained in Arabic learning materials in the book Arabiyah Baina Yadaik for Tsanawiyah students, namely: religious values, ethical values, tolerance values, disciplinary values, complex work values, independent values, democratic values, curiosity values, national spirit values, recognizing excellence, communicative values, reading values, environmental care values and responsibility values and the value of character education values are internalized into the process of Arabic learning stages through teaching materials, learning models and evaluation (authentic assessment).